A prospective longitudinal study testing relationships between meaningful activities, basic psychological needs fulfillment, and meaning in life - Eakman, Aaron M., author; American Occupational Therapy Foundation, publisher (Colorado State University. Libraries, 2014)
The current study used a prospective longitudinal design to determine whether change in meaningful activity over an 11-month period could help explain change in meaning in life in a sample of 174 undergraduate and graduate students. The Engagement in Meaningful Activities Survey, Basic Psychological Needs Scales (i.e., autonomy, competence, relatedness), and the Meaning in Life Questionnaire were used as indicators of the constructs of meaningful activity, basic psychological needs fulfillment, and meaning and purpose in life. The findings were in support of the study hypotheses and indicated that change in meaningful activity explained both change in basic psychological needs fulfillment (i.e., autonomy, competence, relatedness) and change in meaning in life. Further, this study reports findings consistent with results from cross-sectional studies in support of the hypothesis that change in meaningful activity may influence change in meaning in life through two pathways: a direct path of influence from meaningful activity to meaning in life and an indirect path through change in basic psychological needs fulfillment. The current study contributes to a growing literature implicating subjective evaluations of day-to-day action (or meaningful activity) as a fruitful means for exploring relationships between occupation and well-being.
Meaningful activity and meaning in life
Keywords: occupational therapy; human activities; motivation